2002
DOI: 10.1046/j.1365-2958.2002.02912.x
|View full text |Cite
|
Sign up to set email alerts
|

Complementary activities of SseJ and SifA regulate dynamics of the Salmonella typhimurium vacuolar membrane

Abstract: SummaryThe Salmonella pathogenicity island 2 (SPI-2) type III secretion system (TTSS) of Salmonella typhimurium is required for bacterial replication within host cells. It acts by translocating effector proteins across the membrane of the Salmonella-containing vacuole (SCV). The SifA effector is required to maintain the integrity of the SCV membrane, and for the formation in epithelial cells of Salmonella-induced filaments (Sifs), which are tubular extensions of SCVs. We have investigated the role in S. typhim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
288
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(312 citation statements)
references
References 52 publications
21
288
2
Order By: Relevance
“…To estimate bacterial death in the absence of bacterial replication, we used an auxotrophic double mutant strain (aroC purD), which is unable to grow in cultured macrophages (Fields et al, 1986). When assayed in time-course replication assays, the aroC purD mutant strain, which remains within a vacuole throughout the course of the infection (Ruiz-Albert et al, 2002), displayed a fivefold decrease in numbers between 2 and 16 h, in close agreement with the results reported by Buchmeier & Libby (1997) (Fig. 7a).…”
Section: Evidence Of Salmonella Killing In the Cytosol Of Macrophagessupporting
confidence: 84%
See 2 more Smart Citations
“…To estimate bacterial death in the absence of bacterial replication, we used an auxotrophic double mutant strain (aroC purD), which is unable to grow in cultured macrophages (Fields et al, 1986). When assayed in time-course replication assays, the aroC purD mutant strain, which remains within a vacuole throughout the course of the infection (Ruiz-Albert et al, 2002), displayed a fivefold decrease in numbers between 2 and 16 h, in close agreement with the results reported by Buchmeier & Libby (1997) (Fig. 7a).…”
Section: Evidence Of Salmonella Killing In the Cytosol Of Macrophagessupporting
confidence: 84%
“…n et al, 2000). Plasmid pFVP25.1, carrying gfpmut3A under the control of a constitutive promoter, was introduced into bacterial strains Ruiz-Albert et al (2002) for fluorescence visualization where indicated (Valdivia & Falkow, 1997 The infection was allowed to proceed for 15 min at 37 mC in 5% CO # . The monolayers were washed once with DMEM containing FCS and 100 µg gentamicin ml − " and incubated in this medium for 1 h, after which the gentamicin concentration was decreased to 16 µg ml − ".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The T3SS2 effector PipB2 enhances this process likely via direct interaction with kinesin light chain [48,49]. Sif formation involves at least one other T3SS2 effector, the deacylase SseJ, that seems to act as a counter balance to SifA since it down-regulates Sif tubule formation and, unlike the sifA deletion mutant, the double sifA sseJ deletion mutant does not escape from the SCV [50][51][52].…”
Section: T3ss2 Effectors Mediate Intermediate and Late Scv Biogenesismentioning
confidence: 99%
“…The activity of SseJ has been shown to destabilize the SCV membrane in the absence of correct interactions with cytoskeletal motors (described above). Additional deletion of sseJ inhibits the vacuole rupture phenotype of a sifA mutant [34] and the absence of sseJ reduces the vacuole destabilizating affect of myosin II inhibition [6]. Cholesterol affects the fluidity of membranes and it has been suggested that SseJ-dependent cholesterol depletion may contribute to tubulation of the SCV by increasing membrane fluidity while also increasing susceptibility to cytoskeleton motor-dependent forces that cause membrane rupture [32].…”
Section: Role Of Lipids In Vacuole Stabilitymentioning
confidence: 99%